Comparative Metagenomic Analysis of the Gut Microbiota of Captive Pangolins: A Case Study of Two Species - Zhengyu Dai; Bowen Xie; Chungang Xie; Jinsuo Xiang; Xinmei Wang; Jing Li; Rongquan Zheng; Yanni Wang (Animals)
Pangolins, one of the most trafficked mammals, face significant health challenges in captivity, including digestive disorders and immune dysfunctions. These issues are closely linked to alterations in their gut microbiota, which play vital roles in the host metabolism, immunity, and overall health. This study investigated the differences in the gut microbiota composition and function between two pangolin species, Chinese pangolins (Manis pentadactyla) and Malayan pangolins (Manis javanica), under identical captive conditions to better understand their ecological adaptability and health implications. Using metagenomic sequencing, fecal samples from eight adult captive pangolins were analyzed, including four male Malayan pangolins and three male and one female Chinese pangolins. Comparative analyses of the alpha and beta diversities, microbial community structure, and functional profiles were performed. Both species harbored gut microbiota dominated by Firmicutes, Bacteroidetes, and Proteobacteria. However, the Chinese pangolins exhibited higher microbial diversity (Shannon index, p = 0.042; Simpson index, p = 0.037) and lower relative abundance of Proteobacteria compared with the Malayan pangolins. A functional analysis revealed significant differences in the metabolic pathways, where the Chinese pangolins demonstrated a higher potential for fiber degradation, whereas the Malayan pangolins exhibited elevated levels of antibiotic resistance genes and pathogenic taxa, such as Escherichia coli. These findings suggest that captivity duration and environmental stress likely contribute to the observed differences, with the Malayan pangolins experiencing greater dysbiosis due to longer captivity periods. This study provides valuable insights into the role of gut microbiota in pangolin health and offers a foundation for improving conservation strategies and captive care protocols.